IMPLEMENTASI DAN PENGUKURAN LONG TERM EVOLUTION (LTE) DI JAKARTA DAN SEKITARNYA - Muchamad Nur Qosim (Sekolah Tinggi Teknik - PLN, 2016)
This study aims to determine how much readiness in implementing technology Long Term Evolution (LTE), a research model by using measurements in some areas and islands, especially in Jakarta, using a measuring instrument Agilent spectrum analyzer, and with the collection of data online and asked the parties concerned, here in particular with the Ministry of Communications or the Center for Monitoring (Balmon). Results from the study showed that the measurement, which can be no interference with other signals, are still in the corridor on the 2.3 GHz frequency range and the development of the 3GPP technology, with systems that LTE FDD and TDD can be accepted at 1G to 4G networks. LTE technology offers mobile data services in high-speed, reaching 100 Mbps for downlink and 50 Mbps on the uplink. And the measurement results of the average frequency is at 2,383 GH, its bandwidth 9.54 MHz and at the level of the signal - 65.07 dBm. The measurement results can be input to the government restrictions on devices that work in several different frequency bands to avoid interference with users and users between operators.